PENGARUH KEAKTIFAN DALAM KEGIATAN EKSTRAKURIKULER TERHADAP PRESTASI BELAJAR SISWA KELAS X DAN XI SMA NEGERI 1 WONOSARI KLATEN - Ayunesha Awis Wardani; Trisno Martono; Harini Harini (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
This research aimed to find out whether or not there is (1) an effect of students’ activeness in extracurricular activity on learning achievement;and (2) a difference of learning achievement between the students attending extracurricular activity and those not attending.  The population of research was all of the 10th and the 11th graders in SMA Negeri 1 Wonosari Klaten. The sample of research was selected using proportionate random sampling technique. This research employed a descriptive research method with questionnaire technique for the data of students’ activeness in extracurricular and documentation technique for the data of students’ learning achievement. Data analysis was carried out using simple linear regression and independent sample t-test at significance level of 0.10. The results of research were as follows. Firstly, there is a significant effect of the students’ activeness in extracurricular on the students’ learning achievement (t statistic = 2.777 > t table = 1.990 and significance value = 0,004 < 0,10). The students with high score in the activeness in extracurricular activity obtained good learning achievement. Secondly, there was a difference of learning achievement between the students attending extracurricular activity and those not attending (t statistic = 2,458 > t table = 1,6549 and significance value = 0.017 < 0.10). The students attending extracurricular activity better had learning achievement than those not attending.